Integrating genome and transcriptome profiling for elucidating the mechanism of muscle growth and lipid deposition in Pekin ducks - Liyuan Wang (Nature Portfolio, 2017)
Abstract Muscle growth and lipid deposition are co-ordinately regulated processes. Cherry Valley Pekin duck is a lean-type duck breed with high growth rate, whereas the native Pekin duck of China has high lipid deposition. Phenotypic analysis showed that native Pekin ducks have smaller fibre diameter and larger density in the breast muscle at 3 weeks of age and higher intramuscular fat content at 6 weeks of age than those in Cherry Valley Pekin ducks. We detected 17 positively selected genes (PSGs) by comparing genes mainly involved with muscle organ development, muscle contraction, peroxisome proliferator activated receptor signalling pathway, and fatty acid metabolism. In all, 52 and 206 differentially expressed genes (DEGs) were identified in transcriptomic comparisons between the two breeds at 3 and 6 weeks of age, respectively, which could potentially affect muscle growth and lipid deposition. Based on the integration of PSGs and DEGs and their functional annotations, we found that 11 and 10 genes were correlated with muscle growth and lipid deposition, respectively. Identification of candidate genes controlling quantitative traits of duck muscle might aid in elucidating the mechanisms of muscle growth and lipid deposition and could help in improving duck breeding.